Indications of Employee Work Stress Affect the Performance of Employees of Health Facilities - Micko Sigit Wahono (CV. Global Health Science Group, 2022)
Employee performance is a result achieved by the employee in his work according to certain criteria that apply to a particular job. Commitment is needed by the organization so that competent human resources in the organization can be maintained and maintained properly. However, if the commitment of employees who have begun to experience work stress in the work environment will cause a decrease in the level of performance of these employees. The purpose of this study is to determine the indication of employee stress that affects the performance of employees of health facilities. This study is a descriptive qualitative research. Informants in this study amounted to 6 people who work in health facilities X in Yogyakarta. Data collection using field observation, in-depth interviews, and documentation. Data analysis using data reduction, then described in narrative form. Based on the results of this study shows that there are many indications of employee stress that reduces employee performance in health facilities, one of which is work conflict, work culture and workload. Two of the six informants who conducted interviews stated that workload was a major factor in increasing work stress, resulting in boredom in carrying out work routines and decreasing the employee's performance in the assessment every month. Three other people stated that work conflict is a major factor in increasing stress at work, usually occurs between employees in one division who do not agree in carrying out the work. The conclusion that can be drawn is a strong indication of the trigger for increasing work stress and reducing employee performance in health facilities X is excessive and uneven workload, as well as work conflicts between divisions that often occur.